Substrate with laminated film
By placing an antimony-doped tin oxide film on the main material of the low-radiation glass as a heat ray absorption layer and a fluorine-doped tin oxide film as an infrared reflective layer, the problem of difficult to take into account both the thermal barrier properties and the appearance tone in the prior art is solved, and excellent thermal barrier properties and a blue appearance suitable for vehicle use are achieved.
Patent Information
- Application Number
- CN202311361322.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-28
- Filing Date
- 2022-05-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for the existing low-emission glass to achieve excellent thermal barrier properties and appearance tones suitable for vehicle use simultaneously in the thickness adjustment of the functional layer.
A base material with a laminated film is used in which a heat ray absorption layer and an infrared reflective layer is arranged on the main material. The heat ray absorption layer is composed of an antimony-doped tin oxide film, the antimony concentration is controlled at 11.5 mol% or less, and the thickness of the infrared reflective layer is set to 200 nm or more.
It achieves excellent thermal barrier properties and thermal shielding properties of the substrate while maintaining a blue-oriented appearance tone, and is suitable for applications such as roof glass for vehicles.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application date of May 25, 2022 and application number 202280010187.6. Technical Field
[0002] The present invention relates to a substrate with a laminated film, and more particularly, to a substrate with a laminated film suitable for heat shielding of vehicles, buildings, and other structures. Background Art
[0003] Substrates with films, such as glass substrates with thin films and films with thin films, are widely used in various fields as materials satisfying various required properties by laminating functional films on glass or films as main materials.
[0004] For example, in window glass used in vehicles and buildings, low-emissivity glass (Low-E glass) having heat-blocking and heat-shielding properties is used in view of the increasing awareness of energy conservation in recent years. Low-emissivity glass is formed by laminating one or more functional layers containing metal oxides on a glass substrate, and has, for example, a heat ray reflecting layer, a heat ray absorbing layer, a visible light reflecting layer, a visible light absorbing layer, an optical adjustment layer, etc. as functional layers.
[0005] As such low-emissivity glass, for example, Patent Document 1 describes a low-emissivity glass, which includes at least an antimony-containing tin oxide-based film containing antimony and a fluorine-containing tin oxide-based film containing fluorine as metal oxide-based films on the surface of a glass substrate. In addition, Patent Document 2 describes a coated glass product, which includes (a) a glass substrate, (b) an antimony-doped tin oxide coating attached to the above-mentioned glass substrate, and (c) a fluorine-doped tin oxide coating attached to the above-mentioned antimony-doped tin oxide coating, and the thickness of the coating is selected so that the coated glass product has a difference between the visible light transmittance (reference light source C) and the total solar energy transmittance (under the condition of air quality 1.5) on a transparent glass substrate with a nominal thickness of 3 mm, providing a selectivity of 13 or more.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2001-199744
[0009] Patent Document 2: Japanese Patent Application No. 2003-535004 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Low-emissivity glass as described in Patent Documents 1 and 2 obtains heat-shielding properties by a fluorine-doped tin oxide layer on the surface. Furthermore, by adjusting the thickness of the fluorine-doped tin oxide layer, a heat-shielding effect suitable for the use environment can be obtained.
[0012] On the other hand, glass laminates such as low-emissivity glass change color due to the interference effect of light from the functional film. In terms of the color tone of vehicle window glass, red, orange, yellow, etc. are warning colors, so there is a tendency to prefer blue colors as protective colors, and low-emissivity glass with excellent appearance color tone is needed.
[0013] Therefore, an object of the present invention is to provide a substrate with a laminated film which has heat barrier properties and heat shielding properties and has an appearance color tone suitable for vehicle use.
[0014] Means used to solve problems
[0015] The present inventors have conducted intensive research to solve the above-mentioned problems and have found that, in a substrate with a laminated film having a heat ray absorbing layer and an infrared reflecting layer on a main material, the above-mentioned problems can be solved by providing the heat ray absorbing layer with an antimony-doped tin oxide film containing antimony at a specified concentration and by setting the infrared reflecting layer to a specified thickness, thereby completing the present invention.
[0016] The present invention includes the following aspects.
[0017] (1) A substrate with a laminated film, the substrate with a laminated film comprising a main material and a laminated film arranged on the main material, wherein the main material has a first surface and a second surface opposite to each other, the laminated film is arranged on the first surface of the main material, the laminated film has a heat ray absorbing layer and an infrared reflecting layer from a side close to the main material, the heat ray absorbing layer has an antimony-doped tin oxide film, the antimony concentration contained in the heat ray absorbing layer is less than 11.5 mol%, and the thickness of the infrared reflecting layer is greater than 200 nm.
[0018] Effects of the Invention
[0019] The substrate with a laminated film of the present invention can provide a substrate having excellent heat barrier and heat shielding properties and exhibiting a blue color. Therefore, when the substrate with a laminated film of the present invention is used for a roof glass of a vehicle, the appearance is excellent, giving the vehicle body a sense of luxury. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a cross-sectional view of a substrate with a laminated film for explaining the structure of one embodiment of the substrate with a laminated film of the present invention.
[0021] Figure 2It is a cross-sectional view of a substrate with a laminated film for explaining the structure of another embodiment of the substrate with a laminated film of the present invention.
[0022] Figure 3 This is a flow chart schematically showing an example of the method for producing a substrate with a laminated film of the present invention. DETAILED DESCRIPTION
[0023] Hereinafter, the present invention will be described, but the present invention is not limited to the examples in the following description.
[0024] It should be noted that, in this specification, “mass” and “weight” have the same meaning.
[0025] Figure 1 It is a cross-sectional view for explaining the structure of the substrate with a laminated film of the present invention.
[0026] like Figure 1 As shown, the substrate 10 with a laminated film of the present invention comprises a main material 1 and a laminated film 2 arranged on the main material 1. The main material has a first surface 1a and a second surface 1b opposite to each other, and the laminated film 2 is arranged on the first surface 1a of the main material 1. The laminated film 2 has a heat ray absorbing layer 3 and an infrared reflecting layer 5 from the side close to the main material 1.
[0027] Each layer is described below.
[0028] (Main material)
[0029] The main material 1 is the skeleton of the substrate 10 with the laminated film and has self-supporting properties.
[0030] For example, glass, resin, etc. can be cited as the material constituting the main material.
[0031] Examples of the glass include soda-lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, quartz glass, borosilicate glass, and alkali-free glass.
[0032] Examples of the resin include polyolefin resins, polyester resins, polyamide resins, polystyrene resins, polyethylene terephthalate resins, polyvinyl chloride resins, polycarbonate resins, etc. Examples of the polyolefin resin include polyethylene (low-density polyethylene, medium-density polyethylene, high-density polyethylene), polypropylene, polymethylpentene, polybutene, ethylene-propylene copolymers, and ethylene-vinyl acetate copolymers.
[0033] Among them, glass can be suitably used as a main material in the substrate with a laminated film of the present invention.
[0034] The main material may be transparent, translucent or opaque, depending on the application and purpose of the substrate with the laminated film. In addition, the main material may be colorless or colored.
[0035] The shape of the main material is not particularly limited, and may be a plate, a film, a sheet, etc., and may be any shape depending on the intended use. For example, in order to use it in a vehicle member or a building member, a plate is preferred.
[0036] The size of the main material is not particularly limited and can be appropriately adjusted according to the application and purpose of use of the substrate with a laminated film.
[0037] For example, when the substrate with a laminated film is used in a vehicle, a glass plate is preferably used as the main material. The thickness of the glass plate is preferably 1 mm to 5 mm, and the area of the main surface of the glass plate is preferably 0.5 m 2 ~5m 2 In addition, when the substrate with a laminated film is used in a building, a glass plate is preferably used as the main material. The thickness of the glass plate is preferably 4 mm to 8 mm, and the area of the main surface of the glass plate is preferably 0.5 m 2 ~10m 2 .
[0038] (Heat ray absorbing layer)
[0039] The heat ray absorbing layer 3 is a layer that reflects solar radiation heat and imparts heat shielding properties to the substrate with a laminated film, and has crystallinity.
[0040] As materials forming the heat ray absorbing layer, for example, metal oxides such as tin oxide, indium oxide, zinc oxide, titanium oxide, niobium oxide, and tantalum oxide can be cited. In addition, the metal oxide forming the heat ray absorbing layer can be a doped metal oxide doped with other elements (impurity elements). By forming the heat ray absorbing layer with a doped metal oxide, the desired function can be imparted to the heat ray absorbing layer.
[0041] Examples of the impurity element doped into the doped metal oxide include antimony, fluorine, tin, potassium, aluminum, tantalum, niobium, nitrogen, boron, and indium.
[0042] When a doped metal oxide is used in the formation of the heat ray absorbing layer, the concentration of the doped impurity element is preferably 30 mol% or less. When the concentration of the impurity element is 30 mol% or less, the crystal structure before doping can be maintained. The concentration of the impurity element is preferably 30 mol% or less, more preferably 25 mol% or less, and further preferably 20 mol% or less.
[0043] In the present invention, the heat ray absorbing layer has a film containing antimony-doped tin oxide (ATO, a metal oxide obtained by adding Sb to SnO2). The antimony-doped tin oxide film provides excellent heat shielding properties to the substrate with the laminated film by reducing the amount of heat transferred to the inside of the substrate.
[0044] It should be noted that the antimony concentration contained in the heat ray absorbing layer is 11.5 mol% or less. When the antimony concentration in the heat ray absorbing layer is 11.5 mol% or less, it is possible to show heat shielding properties while maintaining the color tone of the substrate with the laminated film to be blue. The antimony concentration contained in the heat ray absorbing layer is preferably 11 mol% or less, more preferably 10.5 mol% or less, and further preferably 10 mol% or less. In addition, from the viewpoint of heat ray absorptivity, the antimony concentration in the heat ray absorbing layer is preferably 3 mol% or more, more preferably 4 mol% or more, and further preferably 5 mol% or more.
[0045] It should be noted that the composition of the heat ray absorbing layer and the concentration of the doped impurity element can be identified by X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS).
[0046] For example, the concentration of antimony (Sb) is analyzed in depth by X-ray photoelectron spectroscopy (XPS) and investigated based on the intensity ratio of Sb and Sn. The concentration of fluorine (F) is analyzed in depth by secondary ion mass spectrometry (SIMS) and investigated based on the intensity ratio of F and Sn. It should be noted that, with respect to SIMS, it is necessary to measure tin oxide SnO2 with a known concentration of added fluorine and to find the coefficient for converting the intensity ratio of F / Sn into the concentration.
[0047] The heat ray absorbing layer may include a single film, or may include two or more films having different materials, metal contents, etc. Among them, the heat ray absorbing layer preferably includes an antimony-doped tin oxide film.
[0048] In the present invention, the thickness of the heat ray absorbing layer is preferably 300nm or more. When the thickness of the heat ray absorbing layer is 300nm or more, sufficient heat shielding is brought to the substrate with the laminated film. In addition, the crystal grains in the heat ray absorbing layer can be grown to a certain extent, so when the infrared reflecting layer is formed, it is easy to increase the crystal grain size in the infrared reflecting layer.
[0049] The thickness of the heat ray absorbing layer is more preferably 350 nm or more, and further preferably 400 nm or more. In view of surface flatness, the thickness of the heat ray absorbing layer is preferably 1000 nm or less, more preferably 900 nm or less, and further preferably 800 nm or less.
[0050] The thickness of the heat ray absorbing layer can be measured by, for example, analysis in the depth direction of X-ray photoelectron spectroscopy.
[0051] It should be noted that since the heat ray absorbing layer is formed by crystal grains of metal oxide, it has a concavo-convex shape on the surface opposite to the main material side. Therefore, the "thickness" of the heat ray absorbing layer varies depending on the location, but in the present invention, it represents the average thickness of the heat ray absorbing layer in the measurement area.
[0052] The size of the crystal grains in the heat ray absorbing layer is preferably 30 nm to 1500 nm. When the crystal grain size is 30 nm or more, the crystal grain shape of the infrared reflecting layer formed on the heat ray absorbing layer can be sufficiently large, resulting in excellent heat barrier properties.
[0053] The grain size is preferably greater than 30 nm, more preferably greater than 50 nm, and further preferably greater than 80 nm. In addition, the larger the grain shape, the better, so there is no particular upper limit, but it is generally preferably less than 1500 nm, more preferably less than 1200 nm, and further preferably less than 1000 nm.
[0054] The size of the crystal grains can be measured by observing a cross section of the substrate with the laminated film cut in the thickness direction using a scanning electron microscope (SEM).
[0055] (Infrared reflection layer)
[0056] The infrared reflecting layer 5 is a layer that reflects infrared rays and imparts heat-shielding properties to the substrate with a laminated film, and has crystallinity.
[0057] Examples of the material forming the infrared reflection layer include doped metal oxides obtained by doping at least one metal oxide selected from the group consisting of tin oxide, indium oxide, zinc oxide, titanium oxide, tantalum oxide, and niobium oxide with other elements (impurity elements).
[0058] Examples of the impurity element to be doped include fluorine, antimony, tin, potassium, aluminum, tantalum, niobium, nitrogen, boron, and indium.
[0059] Specific examples of doped metal oxides include fluorine-doped tin oxide (FTO, a metal oxide obtained by adding F to SnO2), antimony-doped tin oxide (ATO, a metal oxide obtained by adding Sb to SnO2), tin-doped indium oxide (ITO, a metal oxide obtained by adding Sn to In2O3), gallium-doped zinc oxide (GZO, a metal oxide obtained by adding Ga to ZnO), aluminum-doped zinc oxide (AZO, a metal oxide obtained by adding Al to ZnO), tantalum-doped tin oxide (a metal oxide obtained by adding Ta to SnO2), niobium-doped tin oxide (a metal oxide obtained by adding Nb to SnO2), tantalum-doped titanium oxide (a metal oxide obtained by adding Ta to TiO2), niobium-doped titanium oxide (a metal oxide obtained by adding Nb to TiO2), aluminum-doped tin oxide (a metal oxide obtained by adding Al to SnO2), fluorine-doped titanium oxide (a metal oxide obtained by adding F to TiO2), nitrogen-doped titanium oxide (a metal oxide obtained by adding N to TiO2), and the like.
[0060] Among them, the infrared reflecting layer preferably has a film containing a doped metal oxide, which is obtained by doping other elements into at least one metal oxide selected from the group consisting of tin oxide, indium oxide and zinc oxide, and the other elements are preferably at least one selected from the group consisting of fluorine, antimony, tin, gallium and aluminum.
[0061] Specifically, the infrared reflective layer more preferably has a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO) and aluminum-doped zinc oxide (AZO), and from the viewpoint of obtaining higher thermal barrier properties, it is further preferred to have a fluorine-doped tin oxide (FTO) film.
[0062] The infrared reflection layer may include a single film, or may include two or more films having different materials, element contents, and the like.
[0063] The content of the impurity element contained in the infrared reflection layer is preferably in the range of 0.01 mol% to 20 mol%. When the concentration of the impurity element contained in the infrared reflection layer is 0.01 mol% or more, a heat blocking effect can be exhibited, and when the concentration of the impurity element contained in the infrared reflection layer is 20 mol% or less, good crystallinity can be maintained.
[0064] The concentration of the impurity elements contained in the infrared reflecting layer is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, further preferably 0.5 mol% or more. The concentration of the impurity elements contained in the infrared reflecting layer is more preferably 10 mol% or less, further preferably 8 mol% or less, particularly preferably 5 mol% or less.
[0065] It should be noted that, when a plurality of impurity elements are contained in the infrared reflecting layer, the concentration of the impurity elements is the total amount thereof.
[0066] It should be noted that, as described above, the composition of the infrared reflective layer and the concentration of impurity elements can be identified by X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS).
[0067] In the present invention, the infrared reflective layer has a thickness of 200 nm or more. When the infrared reflective layer has a thickness of 200 nm or more, the heat barrier performance of the substrate with a laminated film is improved.
[0068] The thickness of the infrared reflection layer is preferably 205 nm or more, more preferably 210 nm or more, and further preferably 215 nm or more. In addition, as long as the effect of the present invention is achieved, there is no particular restriction on the upper limit of the thickness of the infrared reflection layer. From the viewpoint of ensuring the transmittance of the host material in the visible light region, the thickness of the infrared reflection layer is preferably 1000 nm or less, more preferably 750 nm or less, and further preferably 400 nm or less.
[0069] The thickness of the infrared reflection layer can be measured by depth analysis of X-ray photoelectron spectroscopy or the like.
[0070] When the infrared reflective layer is composed of a plurality of layers of different materials, the “thickness” of the infrared reflective layer is represented by the total of the thicknesses of the respective layers.
[0071] It should be noted that the infrared reflective layer is formed of crystal grains of metal oxide, and the surface of the heat ray absorbing layer stacked with the infrared reflective layer is concavoconvex, so the surface of the layer (i.e., the surface on the side of the heat ray absorbing layer and the surface on the opposite side of the heat ray absorbing layer) has a concavoconvex shape. Therefore, the "thickness" of the infrared reflective layer varies depending on the location, but in the present invention, it represents the average thickness of the infrared reflective layer in the measurement area.
[0072] The crystal grain size in the infrared reflective layer is preferably 30 nm or more. When the crystal grain size is 30 nm or more, the grain boundary scattering of electrons is reduced, the conductivity is improved, and the emissivity is reduced, so that the desired effect of the present invention is easily obtained.
[0073] The grain size is preferably greater than 30 nm, more preferably greater than 50 nm, and further preferably greater than 80 nm. In addition, the larger the grain shape, the better, so there is no particular upper limit, but it is generally preferably less than 1000 nm, more preferably less than 800 nm, and further preferably less than 500 nm.
[0074] In addition, the measurement of the size of a crystal grain can be measured by cross-sectional observation using a scanning electron microscope (SEM) in the same manner as described above.
[0075] The infrared reflective layer preferably has a surface arithmetic mean roughness Ra of 30 nm or less, and more preferably 25 nm or less.
[0076] It should be noted that the heat ray absorbing layer and the infrared reflecting layer are preferably formed by containing the same type of metal oxide. When the metal oxide contained in the heat ray absorbing layer and the metal oxide contained in the infrared reflecting layer are of the same type, the growth of the crystal grains will not be interrupted when the infrared reflecting layer is formed, and the crystal grains in the infrared reflecting layer can be grown larger. For example, when the metal oxide constituting the heat ray absorbing layer is tin oxide, the infrared reflecting layer is preferably a doped tin oxide film.
[0077] The substrate with a laminated film of the present invention preferably has a heat ray absorbing layer comprising an antimony-doped tin oxide (ATO) film, and an infrared reflective layer comprising a fluorine-doped tin oxide (FTO) film. In this configuration, the fluorine concentration contained in the infrared reflective layer is preferably 0.01 mol% to 10 mol%. When the fluorine concentration contained in the infrared reflective layer is 0.01 mol% or more, a sufficient heat barrier effect can be exhibited, and when the fluorine concentration contained in the infrared reflective layer is 10 mol% or less, the mobility of the infrared reflective layer becomes high, and excellent heat barrier properties can be exhibited.
[0078] The concentration of fluorine contained in the infrared reflecting layer is preferably 0.01 mol% or more, more preferably 0.2 mol% or more, further preferably 0.5 mol% or more. In addition, the concentration of fluorine contained in the infrared reflecting layer is more preferably 8.5 mol% or less, further preferably 7 mol% or less, and particularly preferably 6 mol% or less.
[0079] In the present invention, the total thickness of the infrared reflection layer and the heat ray absorption layer is preferably 500nm to 1500nm. When the total thickness of each layer is 500nm or more, the grains in the infrared reflection layer can be fully grown, and when the total thickness of each layer is 2000nm or less, the thickness of the substrate with the laminated film will not become too thick.
[0080] The total thickness of the infrared reflection layer and the heat ray absorption layer is more preferably 550 nm or more, further preferably 600 nm or more, and particularly preferably 650 nm or more. In addition, the total thickness of the infrared reflection layer and the heat ray absorption layer is more preferably 2000 nm or less, further preferably 1500 nm or less, and particularly preferably 1100 nm or less.
[0081] (Optical adjustment layer)
[0082] like Figure 2 As shown, the laminated film 2 in the laminated film-carrying substrate of the present invention may further include an optical adjustment layer 7. When the laminated film-carrying substrate 20 includes the optical adjustment layer 7, the optical adjustment layer 7 is preferably disposed between the host material 1 and the heat ray absorbing layer 3.
[0083] Examples of materials constituting the optical adjustment layer include silicon oxycarbide (SiOC), silicon oxide (SiO2), titanium oxide (TiO2), tin oxide (SnO2), silicon oxynitride (SiON), etc. The optical adjustment layer may include one layer or two or more layers. In addition, the optical adjustment layer may be a mixture of any two or more of the above materials.
[0084] Specifically, as the optical adjustment layer, there can be listed SiOC film, SiOC / SiO2 stacked film stacked in the order of SiOC film and SiO2 film from the main material side, TiO2 / SiO2 stacked film stacked in the order of TiO2 film and SiO2 film from the main material side, SnO2 / SiO2 stacked film stacked in the order of SnO2 film and SiO2 film from the main material side, and the like.
[0085] Among them, from the perspective of alkali metal barrier properties, the optical adjustment layer preferably contains silicon, more preferably has at least one film selected from the group consisting of SiOC film, SiOC / SiO2 stacked film, TiO2 / SiO2 stacked film and SnO2 / SiO2 stacked film, and further preferably has a SiOC film.
[0086] The amount of silicon contained in the entire optical adjustment layer is preferably in the range of 5 mol % to 40 mol %, and more preferably in the range of 10 mol % to 33 mol %.
[0087] The thickness of the optical adjustment layer is preferably 10 nm to 100 nm. When the thickness of the optical adjustment layer is 10 nm or more, the surface of the main material can be evenly covered, and when the thickness of the optical adjustment layer is 100 nm or less, new light interference in the optical adjustment layer can be suppressed, and the optical adjustment layer can exert the desired effect.
[0088] The thickness of the optical adjustment layer is more preferably 20 nm or more, further preferably 25 nm or more, and particularly preferably 30 nm or more. The thickness of the optical adjustment layer is preferably 100 nm or less, more preferably 90 nm or less, and further preferably 80 nm or less.
[0089] In addition, when the optical adjustment layer is composed of multiple layers of different materials, the “thickness” of the optical adjustment layer is represented by the total thickness of each layer.
[0090] (Other layers)
[0091] The substrate with a laminated film of the present invention may have other layers within a range not impairing the effects of the present invention.
[0092] As other layers, an overcoat layer and the like can be cited.
[0093] (Physical properties of substrate with laminated film)
[0094] When the substrate with a laminated film of the present invention is incident with light from a D65 light source at an incident angle of 10 degrees, the chromaticity coordinate a of the reflected color in the L*a*b* colorimetric system is * Preferably it is 2.5 or less. * a * b * In the color system, a * and b * Indicates color and saturation, when a * Big(+a * ) indicates the red direction, when a * Small (-a * ) indicates the green direction, and when b * Big(+b * ) indicates the yellow direction, when b * Small (-b * ) indicates the blue direction. That is, a * and b * The smaller the color, the bluer it is. Compared to warning colors such as red, orange, and yellow, blue is a protective color and is therefore suitable for vehicle window glass and the like.
[0095] when a * When the value is 2.5 or less, the substrate with the laminated film appears blue. From the viewpoint of making the color of the substrate with the laminated film closer to blue, a * The value is more preferably 2.4 or less, further preferably 2.3 or less, and particularly preferably 2.0 or less. In addition, even if green or blue is present, if the color is too strong, the appearance is also impaired, so a * The value is preferably -20 or more, more preferably -10 or more.
[0096] When the substrate with a laminated film of the present invention is incident with light from a D65 light source at an incident angle of 10 degrees, the chromaticity coordinate b of the reflected color in the L*a*b* colorimetric system is * It is preferably less than 2.5. * When the value is 2.5 or less, the substrate with a laminated film appears blue. From the viewpoint of making the color of the substrate with a laminated film closer to blue, b * The value is more preferably 2.4 or less, further preferably 2.0 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less. In addition, even if green or blue is present, if the color is too strong, the appearance is also impaired, so b * The value is preferably -20 or more, more preferably -10 or more.
[0097] When the substrate with a laminated film of the present invention is incident with light from a D65 light source at an incident angle of 10 degrees, the chromaticity coordinates L in the L*a*b* colorimetric system of the reflected color are * Preferably, it is 30.0 to 40.0. * Indicates brightness. For substrates with laminated films that require a deep color, materials with low brightness tend to be preferred. * The value is more preferably 39.0 or less, further preferably 38.5 or less, and particularly preferably 38.0 or less. In addition, the lower limit is preferably 30.0 or more, more preferably 32.0 or more, and further preferably 34.0 or more.
[0098] a * Value, b * Value and L * The value can be measured by an ultraviolet visible spectrophotometer or a colorimeter, and the value when irradiated with light of a D65 light source at an incident angle of 10 degrees is measured using these measuring instruments.
[0099] The substrate with the laminated film preferably has a transmittance based on a standard A light source (Tva, hereinafter also referred to as "A light source transmittance") of less than 30%. When the A light source transmittance (Tva) is less than 30%, sufficient heat ray absorption can be obtained.
[0100] The A light source transmittance (Tva) is preferably 25% or less, more preferably 20% or less, and further preferably 16% or less. In addition, there is no particular restriction on the lower limit, but it is preferably 1% or more, more preferably 2% or more, and further preferably 5% or more.
[0101] The light source A transmittance (Tva) can be measured using a commercially available spectrophotometer (for example, “Lambda 1050” manufactured by PerkinElmer).
[0102] In addition, the solar transmittance (Te) of the substrate with a laminated film is preferably 25% or less. When the solar transmittance (Te) is 25% or less, sufficient heat ray absorptivity can be obtained.
[0103] The solar transmittance (Te) is preferably 25% or less, more preferably 20% or less, and further preferably 15% or less. The lower limit is not particularly limited, but is preferably 1% or more, more preferably 2% or more, and further preferably 5% or more.
[0104] The solar transmittance (Te) can be measured using a commercially available spectrophotometer (for example, “Lambda 1050” manufactured by PerkinElmer).
[0105] The emissivity (En) of the surface of the substrate on the infrared reflective layer side of the laminated film is preferably less than 0.25. When the emissivity (En) of the surface on the infrared reflective layer side is less than 0.25, excellent heat barrier properties can be obtained.
[0106] The emissivity (En) is more preferably 0.22 or less, further preferably 0.20 or less, and particularly preferably 0.15 or less. In addition, the lower the emissivity, the better the thermal barrier properties, so there is no particular restriction on the lower limit of the emissivity, but it is preferably 0.01 or more, more preferably 0.02 or more, and further preferably 0.05 or more.
[0107] Emissivity is the ratio of the energy of light emitted by an object due to thermal radiation (radiant brightness) to the energy of light emitted by a black body at the same temperature (black body radiation) set to 1. The emissivity of the infrared reflecting layer side of the substrate with a laminated film can be measured by the method described in JIS R3106 (2019) using a commercially available emissometer (for example, "Emissometer model AE1" manufactured by Devices & Services).
[0108] In addition, the sheet resistance of the substrate with the laminated film is preferably 30Ω / □ (ohm / square) or less. Emissivity is related to sheet resistance, and when the sheet resistance is 30Ω / □ or less, electricity flows easily, so the emissivity decreases, thereby achieving excellent thermal barrier properties.
[0109] The sheet resistance is preferably 30Ω / □ or less, more preferably 25Ω / □ or less, and further preferably 20Ω / □ or less. In addition, since the lower the sheet resistance, the easier it is for electricity to flow and the lower the emissivity, there is no particular restriction on the lower limit of the sheet resistance, but it is preferably 1Ω / □ or more, more preferably 2Ω / □ or more, and further preferably 3Ω / □ or more.
[0110] The value of the sheet resistance can be determined by Hall effect measurement.
[0111] In addition, the mobility of the substrate with the laminated film is preferably 25 cm 2 / Vs or more. The higher the mobility, the better the conductivity, and the better the thermal barrier. 2 / Vs or more, excellent heat barrier properties can be obtained.
[0112] The mobility is more preferably 27 cm 2 / Vs or more, more preferably 30cm 2 / Vs or more, particularly preferably 35cm 2 / Vs or more. In addition, the higher the mobility, the better, so there is no particular upper limit, but it is preferably 100cm 2 / Vs or less, more preferably 90cm 2 / Vs or less, more preferably 80cm 2 / Vs or less.
[0113] The mobility can be measured by Hall effect measurement.
[0114] In addition, the carrier density of the substrate with the laminated film is preferably 1×10 19 / cm 3 The carrier density refers to the number of free electrons or holes per unit volume in a substance. When the carrier density of the substrate with the laminated film is 1×10 19 / cm 3 When the above values are met, excellent heat barrier properties can be obtained.
[0115] The carrier density of the substrate with the laminated film is more preferably 2×10 19 / cm 3 More preferably, 5×10 19 / cm 3 More than 1×10 20 / cm 3 In addition, the higher the carrier density, the better, so there is no particular upper limit, but it is preferably 1×10 22 / cm 3 Below, more preferably 1×10 21 / cm 3 Below, more preferably 5×10 20 / cm 3 the following.
[0116] In addition, it is preferred that the carrier density of the infrared reflection layer of the substrate with the laminated film is 1×10 19 / cm 3When the carrier density of the infrared reflection layer is 1×10 19 / cm 3 When the above values are met, excellent heat barrier properties can be obtained.
[0117] The carrier density of the infrared reflection layer is more preferably 2×10 19 / cm 3 More preferably, 5×10 19 / cm 3 More than 1×10 20 / cm 3 In addition, the higher the carrier density, the better, so there is no particular upper limit, but it is preferably 1×10 22 / cm 3 Below, more preferably 1×10 21 / cm 3 Below, more preferably 5×10 20 / cm 3 the following.
[0118] The carrier density of the substrate with the laminated film and the infrared reflective layer can be measured by Hall effect measurement.
[0119] In addition, the haze of the laminated film substrate is preferably 10% or less. When the haze is 10% or less, visual white turbidity in the laminated film substrate can be suppressed, and a laminated film substrate having excellent appearance can be obtained.
[0120] The haze is more preferably 9% or less, further preferably 7% or less, and particularly preferably 5% or less. The smaller the haze, the better, so there is no particular lower limit.
[0121] The haze can be measured using a commercially available measuring instrument (for example, a haze meter "HZ-V3" manufactured by Suga Test Instruments Co., Ltd.).
[0122] (Method for producing substrate with laminated film)
[0123] Next, refer to Figure 3 , an example of a method for producing a substrate with a laminated film of the present invention is described.
[0124] It should be noted that, here, as an example, Figure 1 Taking the substrate 10 with a laminated film shown as an example, a method for manufacturing the substrate will be described.
[0125] Figure 3 An example of a flow of a method for producing the substrate 10 with a laminated film is schematically shown.
[0126] like Figure 3 As shown, the method for producing a substrate with a laminated film of the present invention comprises:
[0127] (a) providing a heat ray absorbing layer on the first surface of the main material (step S1), and
[0128] (b) A step of providing an infrared reflecting layer on the heat ray absorbing layer (step S2).
[0129] (Step S1)
[0130] First, prepare the main material. As mentioned above, there is no particular limitation on the type of the main material. For example, when the main material is a glass plate, it can be a soda-lime-silicate high-transmittance glass.
[0131] In step S1 , a heat ray absorbing layer is formed on a first surface of a host material.
[0132] The heat ray absorbing layer can be formed by various film forming methods such as chemical vapor deposition (CVD), electron beam evaporation, vacuum evaporation, sputtering and spraying. Among them, in order to obtain excellent heat ray absorption, Sb needs to replace the Sn site and enter the crystal structure, and a high temperature process is required for this purpose, so it is preferably formed by a thermal CVD method. In addition, when it can be formed by an atmospheric pressure CVD method, a large vacuum device is not required, which can further improve productivity.
[0133] As described above, the heat ray absorbing layer is composed of various thin film materials such as tin oxide, indium oxide, zinc oxide, antimony-doped tin oxide (ATO), fluorine-doped tin oxide (FTO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO), and aluminum-doped zinc oxide (AZO).
[0134] In the present invention, at least an antimony-doped tin oxide (ATO) film is provided as the heat ray absorbing layer.
[0135] For example, a case where an infrared reflection layer is formed of fluorine-doped tin oxide (FTO), a heat ray absorption layer is formed of antimony-doped tin oxide (ATO), and each layer is formed by a thermal CVD method will be described.
[0136] The heat ray absorbing layer uses a mixture of an inorganic or organic tin-containing compound and an antimony-containing compound as a raw material.
[0137] As tin-containing compounds, monobutyltin trichloride (C4H9SnCl3) and tin tetrachloride (SnCl4) can be cited. As tin-containing compounds, organic tin-containing compounds are particularly preferred. When inorganic tin-containing compounds are used as tin-containing compounds, the growth rate of crystal grains is fast and surface irregularities tend to become serious.
[0138] As antimony-containing compounds, antimony trichloride (SbCl3) and antimony pentachloride (SbCl5) can be cited. As antimony-containing compounds, antimony trichloride is particularly preferred. For example, antimony trichloride reacts violently with water in the raw material gas to produce particle clusters of antimony trioxide (Sb2O3) and antimony pentachloride (Sb2O5) in the gas phase. Therefore, by including these particle clusters in the film, the degree of surface unevenness can be controlled.
[0139] In the film formation of the heat ray absorbing layer, the raw material gas may be transported after being mixed in advance. Alternatively, the raw material gas may be mixed on the surface of the main material to be film-formed. In the case where the raw material is liquid, the raw material may be vaporized into a gaseous state using a bubbling method, a vaporization device, or the like.
[0140] The amount of water is preferably set to 5 mol to 50 mol relative to 1 mol of the tin-containing compound in the raw material gas.
[0141] When the amount of water is less than 5 mol, the resistance value of the formed film tends to increase, and as a result, the heat ray absorption function caused by antimony tends to decrease. In addition, the starting point of nucleation decreases, and as a result, the grains tend to grow larger and the surface unevenness tends to become serious. On the other hand, when the amount of water is greater than 50 mol, as the amount of water increases, the raw gas capacity increases, the flow rate of the raw gas increases, and the film forming efficiency may decrease. In addition, the starting point of nucleation increases, and as a result, the grains tend to grow smaller and the surface tends to become flat.
[0142] In the case where the raw material gas contains oxygen, the amount of oxygen is preferably set to be greater than 0 mol and less than or equal to 40 mol, and more preferably set to 4 mol to 40 mol, relative to 1 mol of the tin-containing compound in the raw material gas. When the amount of oxygen is too small, the resistance value of the generated film sometimes increases, so the amount of oxygen is more preferably 4 mol or more. On the other hand, when the amount of oxygen is greater than 40 mol, the raw material gas capacity increases, the flow rate of the raw material gas increases, and thus the film forming efficiency may decrease.
[0143] When the main material is a glass plate, the temperature of the main material when forming the heat ray absorbing layer is preferably 500°C to 650°C.
[0144] When the temperature of the glass is less than 500°C, the formation speed of the heat ray absorbing layer sometimes decreases. In addition, the speed at which the precursor generated by the decomposition of the raw material gas diffuses on the surface of the glass and the heat ray absorbing layer is greater than the speed at which it reacts on the surface of the glass and the heat ray absorbing layer. As a result, more precursors flow into the unevenness on the surface of the glass and the heat ray absorbing layer, and the surface tends to become flat. On the other hand, when the temperature of the glass is greater than 650°C, film formation is carried out in a state where the viscosity of the glass is low, so warping may occur in the process of cooling the glass to room temperature. In addition, the speed at which the above-mentioned precursor reacts on the surface of the glass and the heat ray absorbing layer is greater than the speed at which the above-mentioned precursor diffuses on the surface of the glass and the heat ray absorbing layer. As a result, less precursors flow into the unevenness on the surface of the glass and the heat ray absorbing layer, and the unevenness on the surface tends to become larger.
[0145] When the main material is a resin, the temperature of the main material when forming the heat ray absorbing layer is preferably 30°C to 400°C.
[0146] In the present invention, the antimony concentration in the heat ray absorbing layer is set to 11.5 mol% or less. The antimony concentration in the heat ray absorbing layer can be adjusted by adjusting the amount of the antimony-containing compound relative to the tin-containing compound used, changing the temperature during film formation, changing the ratio of water or oxygen to the tin-containing compound, etc.
[0147] (Step S2)
[0148] Next, an infrared reflecting layer is formed on the heat ray absorbing layer.
[0149] The infrared reflection layer can be formed by various film forming methods such as chemical vapor deposition (CVD), electron beam evaporation, vacuum evaporation, sputtering and spraying, as well as the heat ray absorption layer. Among them, in order to obtain excellent heat barrier properties, it is preferred to form an infrared reflection layer with a large crystal grain size to improve mobility, so it is preferably formed by thermal CVD.
[0150] As described above, the infrared reflection layer can be formed using various thin film materials such as fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO), and aluminum-doped zinc oxide (AZO).
[0151] When the infrared reflective layer is made of, for example, fluorine-doped tin oxide (FTO) or antimony-doped tin oxide (ATO), the surface irregularities of the infrared reflective layer can be increased, making it easier to adjust the color tone to a predetermined range.
[0152] When the infrared reflective layer is composed of, for example, aluminum-doped zinc oxide (AZO) or gallium-doped zinc oxide (GZO), the crystal orientation is easily aligned and the surface is easily flattened.
[0153] In addition, the function of reflecting infrared rays of tin-doped indium oxide (ITO) is strong, and is mostly used in the film thickness region of about 100nm. Therefore, in the case where the infrared reflection layer is composed of tin-doped indium oxide (ITO), it is sometimes difficult to adjust the hue of the reflected color to a specified range, and the growth of the grains is insufficient, and the surface is easily flattened. In addition, ITO uses rare metal In, so it is easy to become expensive. In addition, usually ITO is made by sputtering at a temperature lower than that of thermal CVD method, so from the viewpoint of durability, FTO is preferred.
[0154] For example, when the infrared reflective layer is composed of a fluorine-doped tin oxide layer (FTO) and is formed by a thermal CVD method, a mixture of an inorganic or organic tin-containing compound and a fluorine-containing compound is used as a raw material.
[0155] As the tin-containing compound, as mentioned above, monobutyltin trichloride (C4H9SnCl3) and tin tetrachloride (SnCl4) etc. can be cited. As the tin-containing compound, organic tin-containing compounds are particularly preferred. When an inorganic tin-containing compound is used as the tin-containing compound, the growth rate of the crystal grains is fast, and the surface unevenness tends to become serious.
[0156] Examples of the fluorine-containing compound include hydrogen fluoride and trifluoroacetic acid.
[0157] In the film formation of the infrared reflective layer, the raw material gas may be transported after being mixed in advance. Alternatively, the raw material gas may be mixed on the surface of the film-forming object (specifically, the heat ray absorbing layer). In the case where the raw material material is a liquid, the raw material material may be vaporized into a gaseous state using a bubbling method, a vaporization device, or the like.
[0158] The amount of water is preferably set to 5 mol to 50 mol relative to 1 mol of the tin-containing compound in the raw material gas.
[0159] When the amount of water is less than 5 mol, the resistance value of the formed film tends to increase, resulting in a decrease in infrared reflection function. In addition, the starting point of nucleation decreases, resulting in a large growth of crystal grains and a serious surface unevenness. On the other hand, when the amount of water is greater than 50 mol, as the amount of water increases, the raw gas capacity increases, the flow rate of the raw gas increases, and the film forming efficiency is likely to decrease. In addition, the starting point of nucleation increases, resulting in a small growth of crystal grains and a flat surface.
[0160] When the raw material gas contains oxygen, the amount of oxygen is preferably greater than 0 mol and less than or equal to 40 mol, and more preferably set to 4 mol to 40 mol, relative to 1 mol of the tin-containing compound in the raw material gas. When the amount of oxygen is less than 4 mol, the resistance value of the generated film sometimes increases. On the other hand, when the amount of oxygen is greater than 40 mol, the raw material gas capacity increases, the flow rate of the raw material gas increases, and the film forming efficiency may decrease.
[0161] In the film formation of the infrared reflective layer, the amount of the fluorine-containing compound is preferably set to 0.1 mol to 1.2 mol relative to 1 mol of the tin-containing compound in the raw material gas. When the amount of the fluorine-containing compound is less than 0.1 mol or when the amount of the fluorine-containing compound is greater than 1.2 mol, the resistance value of the formed film tends to increase.
[0162] When a glass plate is used as the main material, the temperature when forming the infrared reflection layer is preferably 500°C to 650°C.
[0163] When the processing temperature is less than 500°C, the formation speed of the infrared reflective layer sometimes decreases. In addition, the speed at which the precursor generated by the decomposition of the raw material gas diffuses on the surface of the glass and the infrared reflective layer is greater than the speed at which it reacts on the surface of the glass and the infrared reflective layer. As a result, more precursors flow into the unevenness of the surface of the glass and the infrared reflective layer, and the surface tends to become flat. On the other hand, when the processing temperature is greater than 650°C, film formation is carried out in a state where the viscosity of the glass is low, so warping may occur in the process of cooling the glass to room temperature. In addition, the speed at which the above-mentioned precursor reacts on the surface of the glass and the infrared reflective layer is greater than the speed at which it diffuses on the surface of the glass and the infrared reflective layer. As a result, less precursors flow into the unevenness of the surface of the glass and the infrared reflective layer, and the unevenness of the surface tends to become larger.
[0164] When the main material is a resin, the processing temperature when forming the infrared reflection layer is preferably 30°C to 400°C.
[0165] It should be noted that step S1 and step S2 can be implemented in-line during the process of making glass using a float glass process, or can be implemented by reheating the glass sheet manufactured by the float glass process in an off-line manner to form a film.
[0166] (Other steps)
[0167] In the present invention, when the optical adjustment layer is provided between the host material and the heat ray absorbing layer, the optical adjustment layer is disposed on the first surface of the host material before step S1.
[0168] The optical adjustment layer can be formed by various film-forming methods such as chemical vapor deposition (CVD), electron beam evaporation, vacuum evaporation, sputtering, chemical plating, wet coating, and spraying, similarly to the heat ray absorbing layer and the infrared reflecting layer. Preferably, the method is the same as that of step S1 and step S2.
[0169] As described above, the optical adjustment layer can be formed using various thin film materials such as SiOC, SiO 2 , TiO 2 , SnO 2 , etc.
[0170] In addition, the optical adjustment layer may include a single layer, or may be a stack of two or more layers.
[0171] For example, when the optical adjustment layer includes a silicon oxycarbide (SiOC) layer, the optical adjustment layer can be formed by an atmospheric pressure CVD method. In this case, as a raw material, for example, a mixed gas including monosilane (SiH4), ethylene and carbon dioxide can be used. When such a carbon-containing gas is used, it is easy to form a particulate silicon compound together with a film-like silicon compound, which can increase the haze rate.
[0172] The raw material gases may be delivered to the first side of the host material after being pre-mixed. Alternatively, the raw material gases may be mixed on the first side of the host material.
[0173] In addition, for example, when the optical adjustment layer includes a silicon oxide (SiO 2 ) layer, as a raw material, for example, a mixed gas of monosilane (SiH 4 ), tetraethoxysilane, oxygen, etc. can be used.
[0174] In addition, for example, when the optical adjustment layer includes a titanium oxide (TiO2) layer, examples of the raw material include tetraisopropyl titanate (TTIP), titanium tetrachloride, etc. Among them, tetraisopropyl titanate (TTIP) is more preferred.
[0175] The temperature of the main material when forming the optical adjustment layer is preferably 500° C. to 900° C. When the temperature of the main material is lower than 500° C. or higher than 900° C., the film formation rate tends to decrease.
[0176] For example, in the case of forming a SiO x C y The layer (hereinafter also referred to as SiO x C y A method of using a layer) as an optical adjustment layer is described below.
[0177] In the CVD method, it is preferred that, for example, a glass plate heated to a temperature of 500° C. to 800° C. is reacted with a gas raw material to form SiO on the glass plate. x C y layer.
[0178] From the viewpoint of increasing the reaction rate of the CVD method, the temperature of the glass plate is preferably 500° C. or higher, more preferably 600° C. or higher, and further preferably 700° C. or higher. From the viewpoint of glass softening, the temperature of the glass plate is more preferably 800° C. or lower, and further preferably 760° C. or lower.
[0179] The gas feedstock preferably comprises a silicon-containing material, an oxidant and an unsaturated hydrocarbon.
[0180] As silicon-containing substances, there can be listed: silanes such as monosilane (SiH4), disilane (Si2H6), dichlorosilane (SiH2Cl2), and silane trioxide (SiHCl3); alkylated silanes such as tetramethylsilane ((CH3)4Si); silicon tetrafluoride (SiF4), silicon tetrachloride (SiCl4), etc., preferably silanes, and more preferably monosilane.
[0181] Examples of the oxidizing agent include compounds containing oxygen elements such as carbon dioxide (CO 2 ), carbon monoxide (CO), oxygen (O 2 ), and water vapor (H 2 O), and carbon dioxide is preferred.
[0182] Examples of the unsaturated hydrocarbons include ethylene-based unsaturated hydrocarbons (olefins), acetylene-based unsaturated hydrocarbons, aromatic compounds, and the like, and compounds that are gaseous at normal temperature and pressure are preferred.
[0183] As the unsaturated hydrocarbon, an olefin is preferred, an olefin having 2 to 4 carbon atoms is more preferred, and ethylene is further preferred.
[0184] By adjusting the mixing ratio of the gas raw materials, the SiO x C y SiO in the layer x C y composition.
[0185] Specifically, the volume ratio of the oxidant to the silicon-containing substance is preferably 8.5 or more, more preferably 12 or more, and even more preferably 20 or more. In addition, the volume ratio of the oxidant to the silicon-containing substance is preferably 50 or less.
[0186] The volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is preferably 0.5 or more, more preferably 1.0 or more. In addition, the volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is preferably 3.5 or less, more preferably 2.7 or less.
[0187] SiO x C y The composition of SiO changes due to the interaction between the above-mentioned oxidant and the unsaturated hydrocarbon. x C yThe composition is adjusted to a preferred range. As for the volume ratio of the oxidant to the silicon-containing substance and the volume ratio of the unsaturated hydrocarbon to the silicon-containing substance, the combination of the two is important, and it is preferred that both be set to the above-mentioned preferred range.
[0188] From the perspective of sufficient coverage, SiO x C y The thickness of the layer is preferably 10 nm or more, more preferably 20 nm or more, and further preferably 25 nm or more. x C y From the viewpoint of light absorption of the layer, the thickness is preferably 90 nm or less, more preferably 80 nm or less, and even more preferably 70 nm or less. x C y The thickness of the layer can be controlled by the type of raw material, raw material gas concentration, the blowing flow rate of the raw material gas to the glass ribbon or glass plate, the substrate temperature, the residence time of the reaction gas from the coating beam structure, etc.
[0189] When an overcoat layer is provided in the present invention, the overcoat layer is disposed on the surface of the infrared reflective layer after step S2.
[0190] The overcoat layer is formed by, for example, a wet method.
[0191] In this case, first, a coating solution for an outer coat layer is prepared.
[0192] The coating solution comprises a precursor of the metal oxide, an organic solvent and water. In addition, particles and / or solid substances may be added to the coating solution. The composition of the particles may be the same as or different from that of the precursor of the metal oxide.
[0193] Next, the coating solution is applied onto the infrared reflective layer of the substrate with the laminated film.
[0194] The coating method is not particularly limited, and a common method such as spin coating can be used.
[0195] Next, the substrate with the laminated film coated with the coating solution is subjected to heat treatment in the air.
[0196] The temperature of the heat treatment is, for example, in the range of 80° C. to 650° C. Moreover, the heating time is, for example, in the range of 5 minutes to 360 minutes.
[0197] The heat treatment can be performed using a common device such as a hot air circulation oven or an IR heating oven. Alternatively, an overcoat layer can be formed from the coating solution by UV curing treatment or microwave treatment.
[0198] Thereby, an overcoat layer can be formed on the infrared reflection layer.
[0199] It should be noted that the above-mentioned heating treatment does not necessarily have to be performed at this stage. That is, the coating solution may also be heated by a heating step performed at another stage.
[0200] Through such steps, the substrate with a laminated film of the present invention can be produced.
[0201] The method for producing a substrate with a laminated film of the present invention may further include a step of air-cooling or chemically strengthening the main material (strengthening step). The strengthening step may be performed in any order, for example, before step S1 or after producing the substrate with a laminated film.
[0202] By performing the strengthening step, when the main material is a glass plate, the strength of the glass plate and the obtained substrate with a laminated film can be improved.
[0203] In addition, after the laminate film is arranged on the main material, the obtained substrate with the laminate film can be bent. Alternatively, when laminated glass is manufactured from the substrate with the laminate film using the glass plate as the main material, a process of bonding another glass plate to the surface of the glass plate side can be implemented.
[0204] Besides this, it will be apparent to those skilled in the art that various modifications can be made.
[0205] The substrate with a laminated film of the present invention can be used for, for example, vehicle window glass (front windshield, rear window glass, side window glass, roof glass, etc.), building window glass, etc., and is particularly suitable for vehicle roof glass.
[0206] As described above, this specification discloses the following aspects.
[0207] <1> A substrate with a laminated film, the substrate with a laminated film comprising a main material and a laminated film arranged on the main material, wherein the main material has a first surface and a second surface opposite to each other, the laminated film is arranged on the first surface of the main material, the laminated film has a heat ray absorbing layer and an infrared reflecting layer from the side close to the main material, the heat ray absorbing layer has an antimony-doped tin oxide film, the antimony concentration contained in the heat ray absorbing layer is less than 11.5 mol%, and the thickness of the infrared reflecting layer is greater than 200nm.
[0208] <2> The substrate with a laminated film as described in <1> above, wherein the infrared reflecting layer has a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide, antimony-doped tin oxide, tin-doped indium oxide, gallium-doped zinc oxide, and aluminum-doped zinc oxide.
[0209] <3> The substrate with a laminated film according to <1> or <2>, wherein the infrared reflective layer comprises a fluorine-doped tin oxide film, and the fluorine concentration contained in the infrared reflective layer is 0.01 mol % to 10 mol %.
[0210] <4> The substrate with a laminated film according to any one of <1> to <3> above, wherein the heat ray absorbing layer has a film thickness of 300 nm or more.
[0211] <5> The substrate with a laminated film according to any one of <1> to <4> above, wherein the transmittance of the substrate with a laminated film based on a standard A light source is less than 30%.
[0212] <6> The substrate with a laminated film according to any one of <1> to <5>, wherein the emissivity of the surface on the infrared reflecting layer side is less than 0.25.
[0213] <7> The substrate with a laminated film as described in any one of <1> to <6> above, wherein when light from a D65 light source is incident at an incident angle of 10 degrees, the chromaticity coordinate a of the reflected color in the L*a*b* colorimetric system is * Below 2.5.
[0214] <8> The substrate with a laminated film as described in any one of <1> to <7> above, wherein when light from a D65 light source is incident at an incident angle of 10 degrees, the chromaticity coordinate b of the reflected color in the L*a*b* colorimetric system is * Below 2.5.
[0215] <9> The substrate with a laminated film according to any one of <1> to <8> above, wherein the mobility of the substrate with a laminated film is 25 cm 2 / Vs or above.
[0216] <10> The substrate with a laminated film according to any one of <1> to <9>, wherein the substrate with a laminated film has a carrier density of 1×10 19 / cm 3 above.
[0217] <11> The substrate with a laminated film according to any one of <1> to <10>, wherein the main material is glass.
[0218] <12> The substrate with a laminated film according to any one of <1> to <11>, wherein the heat ray absorbing layer and the infrared reflecting layer are formed by a thermal CVD method.
[0219] <13> The substrate with a laminated film according to any one of <1> to <12>, wherein the laminated film further includes an optical adjustment layer, and the optical adjustment layer is disposed between the host material and the heat ray absorbing layer.
[0220] <14> The substrate with a laminated film according to <13> above, wherein the optical adjustment layer has at least one film selected from the group consisting of a SiOC film, a SiOC / SiO2 laminated film, a TiO2 / SiO2 laminated film, and a SnO2 / SiO2 laminated film.
[0221] <15> The substrate with a laminated film according to <14> above, wherein the optical adjustment layer includes a SiOC film.
[0222] Example
[0223] The present invention is described in detail below by way of examples, but the present invention is not limited thereto. It should be noted that, regarding the following prepared examples, Examples 1 to 9 and 21 to 28 are examples, and Examples 10 to 20 are comparative examples.
[0224] <Test Example 1>
[0225] In Test Example 1, substrates with laminated films of Examples 1 to 15 were prepared. The measurements performed in Test Example 1 were as follows.
[0226] (Measurement of thickness of each layer)
[0227] The substrate with the laminated film was cut in the thickness direction, and the cross section was observed using a scanning electron microscope (SEM, "SU 70" manufactured by Hitachi, Ltd.).
[0228] In the case where the interface of the heat ray absorbing layer and the infrared reflecting layer can be confirmed by SEM observation, the film thickness of each layer is directly investigated from the SEM image. In the case of unevenness on the interface, the film thickness of each layer is derived while taking the middle line of each horizontal line of the lowest valley and the highest peak as the reference. When the observation magnification is too low, the accuracy of the film thickness measurement is insufficient. On the other hand, when the observation magnification is too high, local unevenness is seen, and it may not be possible to accurately derive the film thickness of each layer, so there is a suitable range. Therefore, as the standard of observation conditions, an electron gun of 1.5kV, a working distance of 2.4mm, and a magnification of 50,000 times are adopted.
[0229] When the interface between the heat ray absorbing layer and the infrared reflecting layer cannot be confirmed by SEM observation, the sum of the film thicknesses of the heat ray absorbing layer and the infrared reflecting layer is investigated from the SEM image, and then the film thickness ratio of the heat ray absorbing layer and the infrared reflecting layer is investigated by depth analysis using X-ray photoelectron spectroscopy (XPS). -6In an XPS chamber of Pa, XPS measurement is performed while etching the film using Ar sputtering. The irradiation area of X-rays is fixed at 100μmφ, and the irradiation angle of X-rays is fixed at 45 degrees. The heat ray absorption layer in this example is an ATO (antimony-doped tin oxide) film, so the midpoint between the point (time) at which the molar ratio of Sb obtained by depth analysis using XPS begins to increase relative to the etching time and the point (time) at which the slope of the increase is approximately zero is set as the interface between the heat ray absorption layer and the infrared reflection layer. In addition, the optical adjustment layer in this example is a SiOC film, so the intersection point where the molar ratios of Sn and Si show the same value is set as the interface between the heat ray absorption layer and the optical adjustment layer. According to this method, the film thickness of each layer can be derived with high reproducibility while referring to the etching rates of the heat ray absorption layer and the infrared reflection layer measured in advance with a single-layer film. In the derivation of the molar ratio of each atom, the software PHI MULTIPAC manufactured by ULVAC is used to calculate the composition based on the X-ray peak intensity. As XPS analysis conditions, the electronic information of O1s, Si2p, Sn3d5 and Sb3d3 orbitals was referenced. However, since the peak positions of O1s and Sb3d5 overlap, in the derivation of the molar ratio of each atom, calibration was performed by subtracting 1.5 times the Sb3d3 peak intensity from the O1s peak intensity based on principle.
[0230] The XPS used the "PHI 5000Versa Probe" manufactured by ULVAC-PHI.
[0231] (Determination of Antimony (Sb) Concentration)
[0232] The antimony concentration was analyzed in the depth direction by X-ray photoelectron spectroscopy (XPS) and investigated based on the intensity ratio of Sb and Sn. The XPS used the "PHI 5000 Versa Probe" manufactured by ULVAC-PHI. The XPS analysis method was the same as that used to evaluate the thickness of each layer.
[0233] (L * 、a * 、b * Determination of
[0234] The chromaticity of the substrate with a laminated film when light from a D65 light source was incident at an incident angle of 10 degrees was measured using a spectrophotometer (“CM-2500d” manufactured by Konica Minolta, Inc.).
[0235] (Determination of Sheet Resistance)
[0236] The substrate with the laminated film was cut into 1 cm squares, and the sheet resistance value was measured using a Hall meter (manufactured by Nanometrics, "HL 5500PC").
[0237] (Measurement of transmittance)
[0238] The transmittance based on the standard A illuminant (Tva, A illuminant transmittance) and the solar transmittance (Te) of the substrate with the laminated film were calculated based on the transmission spectrum measured using the "Lambda 1050" manufactured by PerkinElmer. Te was calculated based on the definition of JISR3106 (2019). Tva was calculated based on the definition of the standard A illuminant.
[0239] (Determination of emissivity)
[0240] The emissivity on the infrared reflecting layer side of the substrate with a laminated film was measured using an "Emissometer model AE1" manufactured by Devices & Services by the method described in JIS R3106 (2019).
[0241] (Measurement of Haze)
[0242] The haze of the substrate with a laminated film was measured using a haze meter "HZ-V3" manufactured by Suga Test Instruments Co., Ltd.
[0243] (Determination of mobility)
[0244] The substrate with the laminated film was cut into 1 cm squares, and the mobility of the layers (heat ray absorbing layer and infrared reflecting layer) flowing in the substrate with the laminated film was measured using a Hall meter ("HL5500PC" manufactured by Nanometrics) (Van der Pauw method).
[0245] (Determination of Carrier Density)
[0246] The substrate with the laminated film was cut into 1 cm squares, and the thin layer carrier density (1 / cm2) of the layers (heat ray absorbing layer and infrared reflecting layer) where electricity flows in the substrate with the laminated film was measured using a Hall meter ("HL 5500PC" manufactured by Nanometrics). 2 ) (Van der Pauw method), and divided it by the sum of the film thicknesses of the heat ray absorbing layer and the infrared reflecting layer, thereby deriving the carrier density (1 / cm) of the portion where the current flows (heat ray absorbing layer and infrared reflecting layer) in the substrate with the laminated film 3 ).
[0247] (Example 1)
[0248] A substrate with a laminated film was produced by the following method.
[0249] First, a glass substrate (soda-lime silicate glass: manufactured by AGC Corporation) having a thickness of 2.1 mm was prepared.
[0250] Next, a SiOC layer was formed on the glass substrate as an optical adjustment layer by thermal CVD method, using monosilane, ethylene, and carbon dioxide as raw material gases and nitrogen as carrier gas, and the target thickness of the SiOC layer was 70 nm.
[0251] Next, a heat ray absorption layer was formed on the SiOC layer. The heat ray absorption layer was antimony-doped tin oxide (SnO2: Sb, ATO), and was formed by thermal CVD. Monobutyltin trichloride (C4H9SnCl3, MBTC), antimony trichloride (SbCl3), water, air, and hydrogen chloride were used as raw material gases, and nitrogen was used as a carrier gas. The target thickness of the heat ray absorption layer was 520nm.
[0252] Next, an infrared reflective layer was formed on the heat ray absorbing layer. The infrared reflective layer was a fluorine-doped tin oxide layer (SnO2:F, FTO), which was formed by thermal CVD. Monobutyltin trichloride (C4H9SnCl3, MBTC), water, air, trifluoroacetic acid (TFA), and nitric acid were used as raw material gases, and nitrogen was used as carrier gas. The target thickness of the infrared reflective layer was 200nm.
[0253] Thus, a substrate with a laminated film was obtained.
[0254] (Examples 2~15)
[0255] A substrate with a laminated film having the layer structure shown in Table 1 was prepared by the same method as in Example 1. The antimony concentration was adjusted by adjusting the ratio of monobutyltin trichloride (MBTC).
[0256] Table 1 shows the measurement results of the substrate with a laminated film in each example.
[0257]
[0258] From the results in Table 1, we can see that in Examples 1 to 9, a * 、b * The values of are all below 2.5, and the hue is blue. Moreover, it can be seen that in any example, the emissivity is less than 0.25, and all have excellent heat barrier properties and heat shielding properties.
[0259] <Test Example 2>
[0260] In Experimental Example 2, the chromaticity coordinates of the reflected color of the substrates with laminated films of Examples 16 to 28 having FTO films of different film thicknesses were evaluated using optical simulation.* Value and a * The value was evaluated.
[0261] For optical simulation, the reflection spectrum was calculated using the Fresnel formula based on the experimentally derived optical constants (refractive index and extinction coefficient) of the ATO film and FTO film. Based on the obtained reflection spectrum, a was calculated according to the definition of JIS (JIS Z 8781-4: 2013). * For the optical constants of the ATO film and the FTO film, the ATO film and the FTO film were formed on a glass substrate, and the ellipsometry spectra were measured using a spectroscopic ellipsometer "M-2000DI" (device name) manufactured by JA Woollam, and derived using analysis software WVASE32 manufactured by JA Woollam.
[0262] Table 2 shows the results.
[0263] Table 2
[0264]
[0265] According to the results in Table 2, it can be seen that the thickness of the FTO film is more than 200 nm. * When the value is below 2.5, the hue appears blue.
[0266] Although the present invention is described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the subject matter and scope of the present invention. This application is based on Japanese patent applications (Japanese patent applications 2021-091745) filed on May 31, 2021 and Japanese patent applications (Japanese patent applications 2021-214754 and Japanese patent applications 2021-214755) filed on December 28, 2021, the contents of which are incorporated herein by reference.
[0267] Description of symbols
[0268] 1 Main material
[0269] 1a Side 1
[0270] 1b Side 2
[0271] 2 Laminated Film
[0272] 3 Heat ray absorption layer
[0273] 5 Infrared reflection layer
[0274] 7 Optical adjustment layer
[0275] 10, 20 Substrate with laminated film
Claims
1. A substrate with a laminated film, the substrate with a laminated film comprising a main material and a laminated film arranged on the main material, wherein: The main material has a first surface and a second surface opposite to each other, and the laminated film is arranged on the first surface of the main material. The laminate film has a heat ray absorbing layer and an infrared ray reflecting layer from a side close to the main material, The heat ray absorbing layer comprises an antimony-doped tin oxide film, the antimony concentration contained in the heat ray absorbing layer is 11 mol % or less, and the film thickness of the heat ray absorbing layer is 350 nm or more, The infrared reflection layer has a thickness of 200 nm or more. The visible light transmittance of the substrate with the laminated film based on a standard A light source is 25% or less.
2. A substrate with a laminated film, the substrate with a laminated film comprising a main material and a laminated film arranged on the main material, wherein: The main material has a first surface and a second surface opposite to each other, and the laminated film is arranged on the first surface of the main material. The laminate film has a heat ray absorbing layer and an infrared ray reflecting layer from a side close to the main material, The heat ray absorbing layer comprises an antimony-doped tin oxide film, the antimony concentration contained in the heat ray absorbing layer is 10 mol % or less, and the film thickness of the heat ray absorbing layer is 400 nm or more, The infrared reflection layer has a thickness of 200 nm or more. The visible light transmittance of the substrate with the laminated film based on a standard A light source is 25% or less.
3. The substrate with a laminated film according to claim 1 or 2, wherein The infrared reflection layer includes a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide, antimony-doped tin oxide, tin-doped indium oxide, gallium-doped zinc oxide, and aluminum-doped zinc oxide.
4. The substrate with a laminated film according to claim 1 or 2, wherein The infrared reflection layer includes a fluorine-doped tin oxide film, and the fluorine concentration contained in the infrared reflection layer is 0.01 mol % to 10 mol %.
5. The substrate with a laminated film according to claim 1 or 2, wherein The emissivity of the side surface of the infrared reflection layer is less than 0.
25.
6. The substrate with a laminated film according to claim 1 or 2, wherein The emissivity of the side surface of the infrared reflection layer is less than 0.
15.
7. The substrate with a laminated film according to claim 1 or 2, wherein When the light from the D65 light source is incident at an angle of 10 degrees, the chromaticity coordinate a of the reflected color in the L*a*b* color system is * Below 2.
5.
8. The substrate with a laminated film according to claim 1 or 2, wherein When the light from D65 source is incident at an angle of 10 degrees, the chromaticity coordinate b of the reflected color in the L*a*b* color system * Below 2.
5.
9. The substrate with a laminated film according to claim 1 or 2, wherein The mobility of the substrate with the laminated film is 25 cm 2 / Vs or above.
10. The substrate with a laminated film according to claim 1 or 2, wherein The carrier density of the substrate with the laminated film is 1×10 19 / cm 3 above.
11. The substrate with a laminated film according to claim 1 or 2, wherein The main material is glass.
12. The substrate with a laminated film according to claim 1 or 2, wherein The main material is transparent.
13. The substrate with a laminated film according to claim 1 or 2, wherein The laminated film further includes an optical adjustment layer disposed between the host material and the heat ray absorbing layer.
14. The substrate with a laminated film according to claim 13, wherein The optical adjustment layer has at least one film selected from the group consisting of a SiOC film, a SiOC / SiO 2 stacked film, a TiO 2 / SiO 2 stacked film, and a SnO 2 / SiO 2 stacked film.
15. The substrate with a laminated film according to claim 14, wherein The optical adjustment layer has a SiOC film.
16. A method for producing a substrate with a laminated film, which is the method for producing a substrate with a laminated film according to any one of claims 1 to 15, wherein: The heat ray absorbing layer and the infrared reflecting layer are formed by a thermal CVD method.
Citation Information
Patent Citations
Low radiation glass and glass article using the low radiation glass
JP2001199744A
Glass products with solar control coatings
JP2003535004A
Method for producing carbon fiber composite material, and carbon fiber composite material
JP2021091745A